2018
DOI: 10.1021/jacs.8b09232
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Arene Synthesis by Annulative π-Extension

Abstract: Annulative π-extension (APEX) has emerged as a powerful and efficient synthetic method for the construction of polycyclic aromatic hydrocarbons, nanographenes, and π-extended fused heteroarenes. In contrast to classical multistep syntheses requiring substrate prefunctionalization, APEX reactions minimize the number of preparative steps by direct C−H activation of small aromatic templates. In this Perspective, we review recently reported APEX reactions to shed light on the utility, scope, and promise of this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(126 citation statements)
references
References 99 publications
0
122
0
4
Order By: Relevance
“…Smith and Lucas have reported the synthesis of interesting tetraarylene-bridged cavitands based on resorcin [4]arene using FeCl 3 or DDQ as the oxidants. [222] Helicenes have fired researchers imagination ever since the first synthesis and resolution of [6]helicene in 1956.…”
Section: Curved Twisted and Strained Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith and Lucas have reported the synthesis of interesting tetraarylene-bridged cavitands based on resorcin [4]arene using FeCl 3 or DDQ as the oxidants. [222] Helicenes have fired researchers imagination ever since the first synthesis and resolution of [6]helicene in 1956.…”
Section: Curved Twisted and Strained Structuresmentioning
confidence: 99%
“…These reactions are often the methods of choice for the synthesis of large p-extended scaffolds as well as smaller benzenoid or heteroaromatic compounds possessing biaryl linkages (Scheme 1). TheS choll reaction is undoubtedly the most useful for the construction of nanographenes [4,5] and their heterocyclic analogues. [6] Indeed, in some cases,m ore than 100 CÀCbonds are formed in one synthetic operation to furnish truly amazing polycyclic aromatic hydrocarbons from suitable precursors.T here is no other reaction that can duplicate this result for ad iscrete molecule (i.e.n ot ap olymer).…”
Section: Introductionmentioning
confidence: 99%
“…Thes ynthesis of PA Hs through multiple,s imultaneous carbon-carbon cross-coupling (CÀHactivation) reactions has also been reported by Itami and co-workers. [110,111] With ar eaction called annulative p-extension (APEX), they showed that the K-region of aP AH can react with silol derivatives in the presence of acationic palladium catalyst in the presence of o-chloranil as an oxidant to give longer PA Hs as exemplified in Scheme 8( compounds 41 and 43). [112] The same group showed that the silol derivatives can be replaced…”
Section: Gnrs From Palladium-catalyzed Reactionsmentioning
confidence: 99%
“…One-step p-extension of unfunctionalized (hetero)arenes is considered an efficient approach in achieving rapid access to fused aromatics such as N-PACsa nd nitrogen-doped nanographenes.R ecently,w ef ormulated APEX (annulative p-extension) as an step/atom-economical strategy for arange of fused p-conjugated systems,a nd developed several new catalytic carbon-based APEX reactions for the rapid synthesis of polycyclica romatic hydrocarbons (PAHs), nanographenes,and graphene nanoribbons. [6,7] If one could develop an APEX reaction to construct new fused heteroaromatic rings,that is,hetero-APEX, [8] the accessibility and utilization of emerging N-PACsand nitrogen-doped nanographenes will be significantly enhanced. Recently,the groups of Mal, [8a] and Nozaki and Ito [9] reported one-step and two-step aza-APEX reactions that construct new pyrrole rings onto benzene, naphthalene,a nd corannulene (Figures 1a and b).…”
Section: Introductionmentioning
confidence: 99%